Innovation in Literacy Teaching: Reading and Writing Techniques Training for Elementary School Teachers - Jumrah, Abrina Maulidnawati; Irviana, Ira; Nurdiansyah, Erwin; Musbaing, Musbaing; Syastiawan, Andi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
Literacy is a fundamental skill that forms the foundation for all learning processes in elementary schools. This community service activity aims to improve elementary school teachers' competence in applying innovative techniques in reading and writing instruction through systematic and comprehensive training. The method used is participatory training with an andragogic approach that includes interactive workshops, teaching practice simulations, group discussions, and continuous mentoring. The activity was carried out for four months involving 20 elementary school teachers from Biringkanaya District, Makassar. The instruments used included teacher competency tests in literacy, teaching practice observation sheets, and program evaluation questionnaires. The results of the activity showed a significant increase in teacher competence by 82.3% from pre-test to post- test scores. Teachers' ability to design innovative literacy learning increased from 58.7% to 91.4%. The application of creative reading and writing techniques also experienced substantial improvement from 62.1% to 88.9%. This activity has a positive impact on the quality of literacy learning in elementary schools in Biringkanaya District and can be a replication model for other similar schools.